2014
DOI: 10.1155/2014/273908
|View full text |Cite
|
Sign up to set email alerts
|

Potential Interaction of Green Tea Extract with Hydrochlorothiazide on Diuretic Activity in Rats

Abstract: Treatment of ischemic hypertensive patients with hydrochlorothiazide can precipitate cardiac arrhythmias. The present study was undertaken to evaluate the diuretic potential of green tea alone and its effects on hydrochlorothiazide in interactive groups. Rats were treated with high (500 mg/kg, p.o.) and low (100 mg/kg, p.o.) dose of green tea extract in alone and interactive groups for 30 days. Standard, high, and low dose interactive groups received hydrochlorothiazide (10 mg/kg, p.o.) on the day of experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Chakraborty et al were the first to study the effects of green tea alone and in combination with hydrochlorothiazide (HCTZ) on diuretic activity. The results showed that green tea extract at doses of 100 and 500 mg/kg showed significant diuretic activity; furthermore, green tea extract also significantly reduced potassium loss in the combination group compared with the HCTZ-treated group alone [115]. Susilowati et al (2019) also reported that green tea extract at a dose of 70 mg/kg had diuretic activity equivalent to furosemide, which may be related to the increase of glomerular filtration rate by increasing blood flow and cardiac output to the kidneys [116].…”
Section: Other Pharmacological Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Chakraborty et al were the first to study the effects of green tea alone and in combination with hydrochlorothiazide (HCTZ) on diuretic activity. The results showed that green tea extract at doses of 100 and 500 mg/kg showed significant diuretic activity; furthermore, green tea extract also significantly reduced potassium loss in the combination group compared with the HCTZ-treated group alone [115]. Susilowati et al (2019) also reported that green tea extract at a dose of 70 mg/kg had diuretic activity equivalent to furosemide, which may be related to the increase of glomerular filtration rate by increasing blood flow and cardiac output to the kidneys [116].…”
Section: Other Pharmacological Effectsmentioning
confidence: 97%
“…In vivo [112] Diuretic activity Green tea extract 100~500 mg/mL In vivo [115] Bone-protective effect green tea polyphenols 0.1% or 0.5% concentration In vivo [117] Anti-protozoal Leishmania effect EGCG and ECG IC 50 = 27.7, 75 µM, respectively In vitro [118] and cardiac output to the kidneys [116].…”
Section: Effects On the Immune Systemmentioning
confidence: 99%
“…Furthermore, other studies state that flavonoids can increase urine volume as these compounds increase the rate of glomerular velocity (Jouad et al, 2001). Chakraborty et al (2014) prove that the flavonoids contained in green tea are responsible for inhibiting the activity of the angiotensin-converting enzyme (ACE). Green tea can inhibit ACE activity through the mechanism of mixed inhibition, and ACE inhibition is one of the main reasons for diuretic activity and increased Na + concentrations in urine.…”
Section: Diuretic Effectsmentioning
confidence: 99%
“…They are also particularly useful in preventing stroke and heart failure in hypertensive patients (Grossman et al, 2011). The green tea leaf extract, when combined with hydrochlorothiazide, has been proven to significantly increase diuretic activity (Chakraborty et al, 2014). Regular consumption of green tea may also provide some protection against hypertension in humans (Negishi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation